Ethyl acetate fraction of Mucuna pruriens leaves mitigates diclofenac-induced hepatotoxicity via modulation of biochemical and histological parameters changes in Wistar Rats - Oladapo Oyinloye; Abdullahi Murtala; Farouk Oladoja; Olufemi Okunye; Emmanuel Kasumu; Peter Iloka (Pensoft Publishers, 2023)
Mucuna pruriens contains saponins and flavonoids, which help to decrease cholesterol, treat hypertension, provide protein and vitamins and prevent premature ageing. This research followed the NIH guidelines (NIH publication 85-23, revised in 1996). Rats weighing 200-250 g were assigned into six groups (n = 6), normal saline only (control), normal saline (NS), Ethyl acetate fraction of Mucuna pruriens leaves (EAFMP) (100, 200 and 400 mg/kg) and Silymarin (100 mg/kg) treated orally for five days, diclofenac (DFN) was administered on days 3 and 4 via intraperitoneal route, biochemical and histology parameters were determined in serum and liver. This research revealed that treatment with EAFMP reversed the elevation of liver enzymes, total bilirubin, LDL and total cholesterol and lipid peroxidation; liver SOD, GSH, and CAT were elevated in EAFMP and Silymarin groups. The hepatic histological lesions in EAFMP were reduced in a dose-dependent manner. This research shows that EAFMP attenuates the deleterious effect of diclofenac-induced liver toxicity in rats.